A Middle East systematic review and meta-analysis of prevalence and antibiotic susceptibility pattern in MRSA Staphylococcus aureus isolated from patients with cystic fibrosis - Yousef Nikmanesh; Afsaneh Foolady Azarnaminy; Pourya Avishan; Mohammadreza Taheri; Paniz Sabeghi; Ehsan Najibzadeh; Azad Khaledi (BMC, 2022)
Abstract Background This study aimed to determine the prevalence and antibiotic resistance patterns in Staphylococcus aureus isolated from patients with cystic fibrosis in Middle Eastern countries. Methods A systematic search was conducted in the PubMed, Web of Science (ISI), and Scopus databases for studies presenting the prevalence of MRSA strains, antibiotic resistance pattern in S. aureus strains isolated from patients who suffered from cystic fibrosis in Middle Eastern countries from 1999 to 10 June 2020. The following terms were used; prevalence, antibiotic resistance, antimicrobial drug resistance, drug resistance, Staphylococcus aureus, S. aureus, Methicillin-resistant Staphylococcus aureus, MRSA, cystic fibrosis, CF, and the Middle East. The meta-analysis was performed using Comprehensive Meta-analysis software (Version 3.3.070). Results Patients' age ranged from 1.6 to 18 years. Females were more than males. The prevalence of S. aureus was varied between 5.6 and 77.8%. The prevalence of S. aureus was varied between 5.6 and 77.8% in different countries. The combined prevalence of S. aureus in Middle East countries from 1999 to 2020 was reported by 40.9% (95% CI 29.6-53.1). The pooled prevalence of MRSA was reported at 18.6% (95% CI 1.1-82.6), Z = 0.9, I 2 = 98.6, Q = 146.7. The highest combined resistance in S. aureus strains was reported to Penicillin G (94%), followed by Ciprofloxacin (54.9%). Conclusion Regarding a quite prevalence of S. aureus and an intermediate prevalence of MRSA in CF patients, preventive measures and health policies should be implemented in the Middle East area to prevent the spread of infections caused by MRSA strains in CF patients.